Theoretical and experimental study on the effect of plane diaphragm tension on hydroelastic coupled vibrations in a hemispherical tank. (August 2022) - Chiba, M.; Shigematsu, S.; Motoyama, N.
Abstract: In this study, to simulate liquid sloshing in a spacecraft fuel tank, the effect of tension of a plane diaphragm on the hydroelastic coupled vibration of the liquid in a hemispherical tank was investigated both analytically and experimentally. In the theoretical analysis, the liquid was assumed to be incompressible, non-viscous, and irrotational, and the plane diaphragm corresponded to a clamped circular membrane. The influence of tension of the diaphragm on the natural frequency was investigated. In addition, its natural frequencies and vibration modes were compared with those of a liquid in a cylindrical tank. The comparison revealed that the natural vibration characteristics of a liquid in a hemispherical tank approximate those of a liquid with the same volume in a cylindrical tank. In the experiment, two silicon test membranes with diameters of 500 mm, one 0.22 mm thick and the other 0.34 mm thick, were used as plane diaphragms. Each test membrane was uniformly tensioned in the radial direction at ten points that were uniformly spaced along the circumference of the edge of the membrane. The natural frequencies were measured by tapping the test membranes with a finger and conducting an FFT analysis of the response. The vibration modes were measured by exciting the membranes acoustically and measuring their responses using a scanning laser Doppler vibrometer. A comparison between the experimental and theoretical results showed that they were in good agreement, even in the case of an empty tank. This demonstrates the validity of the theoretical analysis and accuracy of the experimental results. Highlights: Investigated effect of tension on hydroelastic coupled vibration of liquid in tank covered with plane diaphragm from both theoretically and experimentally. Two test silicon membranes used as plane diaphragms were uniformly tensioned. Sloshing characteristic of liquid in a hemispherical tank covered with plane diaphragm can be approximated with that of liquid having the same volume in a cylindrical tank. Experimental results and theoretical results showed good agreement.